Destination image during the COVID-19 pandemic and future travel behavior: The moderating role of past experience. (September 2021) - Rasoolimanesh, S.Mostafa; Seyfi, Siamak; Rastegar, Raymond; Hall, C.Michael
Abstract: This study investigates the effects of cognitive destination image shaped by media during the COVID-19 pandemic on willingness to support and post-pandemic travel intention. Drawing upon the concept of cognitive destination image and through an online self-administered survey, the effects of four factors including trust, crisis management, healthcare system, and solidarity on travel behavioral intention are compared based on tourists' prior experience of a given destination. To achieve this aim, ten countries with different coping strategies, numbers of positive cases and mortality rate were studied. A total number of 518 useable questionnaires were collected from the prospect international tourists who followed news related to COVID-19 for one of the selected countries and plan to travel in the future. Partial least squares – structural equation modeling and multi-group analysis were used to test the model and hypotheses. The results showed the high predictive power of the model on post COVID-19 travel behavioral intention. The findings revealed the strong and positive effects of trust and healthcare system on behavioral intention of respondents without past experience to visit a destination, whereas the effect of solidarity on behavioral intention was identified much stronger for the prospect tourists with past experience of visiting a destination. This research provides unique theoretical contributions by investigating the effects of trust, crisis management, healthcare system, and solidarity shaped by media during COVID-19 outbreak as the components of cognitive destination image on future behavioral intention across past experience of visiting a destination. This study also provides insights on post-crisis recovery factors affecting travel behavioral intention and demand. Highlights: Media-framed destination image was a significant trigger of post-pandemic behavioural intent. Trust and healthcare system positively impact travel intention for those without past experience. Solidarity positively impacts travel intention for those with past experience.